Fabricate : rethinking design and construction (2019)
So, here we are with the third iteration of the built environment’s thinking and making triennial celebration: FABRICATE 2017. What began as a polar comparison between the 2011 and 2014 events has developed into a series through which to take stock of the fast-changing fabrication design landscape. Rather than simply revealing greater sophistication and quicker processes six years after the inaugural event, we believe that the contents of this volume attest to a seismic shift in both professional outreach and construction application, and to a striking expansion in the field of players. Surveying this landscape, practices, industries and design education institutions have even more to draw upon that will boost their confidence as regards the required time commitment and budget to push research and education in fabrication further. Shifts in perspective concomitant with greater investment will be rewarded by the cultural and practical benefits of adventurous, high quality, responsive architecture produced with correspondingly reduced costs and minimised environmental impact. Looking beyond the immediate glamour of FABRICATE, these benefits are the ultimate endgame.